RASIO INTERKAUDATUS SEBAGAI PREDIKTOR PELEMAHAN KOGNITIF STUDI KORELASI ANTARA SKOR CDT DENGAN RASIO INTERKAUDATUS PADA PENILAIAN FUNGSI KOGNITIF LANSIA - Wijoto*, Mardiana W* (Neurona Majalah Kedokteran Neuro Sains, 2011)
INTRODUCTION MOST OF COGNITIVE IMPAIRMENT FREQUENTLY FOUND IN GERIATRIC BUT OFTEN THE DOCTORS AND THE PATIENT DID NOT REALIZE OTHERWISE USING HEAD CT SCAN OFTEN COULD BE PERFORMED TO MAKE A DIAGNOSIS OR AN EVALUATION FOR SOME INTRACRANIAL ABNORMALITY INCLUDING COGNITIVE IMPAIRMENT CAUSED BY CAUDATE ATROPHY THE IMPORTANT ROLES OF CAUDATE NUCLEI ARE PROCESSES OF EXECUTIVE FUNCTIONS CAUDATE ATROPHY COULD BE MEASURE BY INTERCAUDATUS RATIO ICR USING HEAD CT SCAN